Prevention of Financial Law Violations - Khatamov Adham Sobirovich (Scientific Trends, 2025)
This scientific article examines the issue of preventing financial law violations. The article analyzes the main types of financial law violations, their causes and consequences, as well as international and national experiences in combating this problem. Mechanisms for combating financial law violations in the conditions of Uzbekistan and measures necessary for their effective implementation are proposed. The article shows the importance of modern technologies, increasing legal literacy and strengthening control systems in preventing financial law violations. This study considers prospects for improving financial regulation and combating corruption.
Keywords: Financial law violations, corruption, tax evasion, financial fraud, digital technologies, financial control, international experience, Uzbekistan, financial monitoring, legal literacy, financial system, fight against corruption, electronic monitoring, blockchain, tax legislation.